Influence of chlorhexidine and zinc oxide in calcium hydroxide pastes on pH changes in external root surface - Thiago Farias Rocha LIMA; Juliane Fabrício ASCENDINO; Isabelly de Oliveira CAVALCANTE; Fabio Luiz Cunha D´ASSUNÇÃO; Juan Ramon SALAZAR-SILVA; Emmanuel João Nogueira Leal da SILVA; Sherlan Guimarães LEMOS; Adriana de Jesus SOARES (Sociedade Brasileira de Pesquisa Odontológica, 2019)
Abstract The objective of this study was to assess the influence of chlorhexidine (liquid and gel) and zinc oxide in calcium hydroxide (CH) pastes on root pH in simulated external resorption. One hundred human anterior teeth with a single root canal were selected. After decoronation and root canal instrumentation, the specimens were divided into 4 experimental groups and 1 control group (without intracanal paste): CH + saline (CH+S), CH + 2% chlorhexidine liquid (CH+ CHX), CH + 2% chlorhexidine gel (CH+ CHXg), and CH + 2% chlorhexidine gel + zinc oxide (CH+ CHXg+ZnO). pH was measured using a microelectrode at 3 and 24 h, and 1, 2, 3, and 4 weeks after inserting intracanal pastes. Data were analyzed statistically using an ANOVA and Tukey's test (p < 0.05). The CH+CHXg+ZnO group had the highest pH values throughout (p<0.05). The CH+S and CH+ CHX groups had the highest pH values after 1 week and the CH+ CHXg group after 2 weeks. CH+ CHXg maintained the highest pH until the fourth week compared with CH+ CHX (p < 0.05). The control group remained at a neutral pH at all evaluated times. It can be concluded that chlorhexidine solution or gel maintained the alkaline pH of CH, and chlorhexidine gel allowed a slower decrease in pH over time. CH+ CHXg+ZnO showed the highest pH values and was an effective intracanal medication for maintaining alkaline root pH in the area of resorption.